Tawuran Antar Basis sebagai Bentuk Penyimpangan Sosial di Kalangan Remaja Perkotaan dalam Perspektif Differential Association Theory - Ciek Julyati Hisyam; Mayang Puti Seruni; Alya Fatma Hadi; Dina Lestari; Fatimah Az-Zahra; Ginola Muhammad Safier; Nadiya Salsabila (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The phenomenon of gang fights between groups has become a serious problem for all parties. Gang fights reflect the fragility of social control and the weak internalization of values of discipline and tolerance among teenagers. In addition, the cause of gang fights carried out by a number of students is based on pride and environmental influences that encourage them to engage in deviant behavior or even criminal acts. This study aims to describe the definition and characteristics of gang fights, examine gang fights as a form of social deviance, and identify the social deviance impacts caused by gang fights. This study uses a qualitative approach. Data collection was conducted through in-depth interviews and literature review. The study concluded that forms of social deviance such as gang fights are learned through intensive social interaction within peer groups, as explained by Differential Association Theory. Thus, gang fights as deviant behavior do not simply arise spontaneously, but are the result of a continuous social learning process in a supportive environment, where values of violence and group solidarity are formed and passed down from one individual to another.